Menelaah Pesan Pemerintah Terkait Krisis Covid-19 di Media Sosial - Dewa Ayu Diah Angendari (Jurnal Riset Komunikasi, 2021)
As the Covid-19 health crisis spreads, the level of uncertainty in the community is getting higher. The government has a responsibility to reduce uncertainty by providing the right message to the affected public. In Indonesia, the Ministry of Health (Kemenkes) and the Covid-19 task force (Task Force Covid-19) became two agencies that actively provide information related to Covid-19. This research aims to descriptively explain the message conveyed by both agencies related to Covid-19 through content analysis. The study results found that both the Ministry of Health and the Covid-19 Task Force emphasized messages related to the efforts made by the government to deal with the spread of Covid-19, the development of case numbers, and the recommendation of the adoption of health protocols. However, the two agencies did not give enough portions to the message explaining the current crisis and sympathy to the public. Explanations of the situation can encourage the public to adopt government advice, while expressions of sympathy are needed in crises to provide a sense of security amid uncertainty.